Pengaruh Prinsip Tata Kelola Terhadap Kinerja Keuangan pada Badan Usaha Milik Desa (BUMDes) di Kabupaten Badung - Ni Komang Novi Antari; Sang Ayu Putu Arie Indraswarawati; Ni Putu Yeni Yuliantari (UNHI Press, 2026)
This research seeks to examine the application of governance practices and their influence on the financial performance of Village-Owned Enterprises (BUMDes) in Badung Regency. A quantitative approach was employed, utilizing multiple linear regression analysis. The study population comprised all 120 BUMDes employees in Badung Regency. Using purposive sampling, the research obtained 120 respondents, which included chairpersons, treasurers, and unit heads. The findings reveal that the principles of cooperation, participation, emancipation, transparency, accountability, and sustainability significantly and positively affect financial performance. The adoption of sound governance practices has been demonstrated to enhance the financial outcomes of BUMDes. These results offer practical implications, emphasizing the need for BUMDes managers to prioritize governance principles to strengthen overall organizational performance.